DO DIREITO CULTURAL DAS PESSOAS COM DEFICIÊNCIA - Patrícia Silva Dorneles; Claudia Reinoso Araujo de Carvalho; Ana Cecília Chaves Silva; Vânia Mefano (Revista de Políticas Públicas, 2018)
This article aims to present the institution of the agenda of cultural citizenship of people with disabilities next to the national culture policy. Although the agenda is still fragile, it obseves the initiatives until now implemented through accessible cultural actions, projects, programs and policies have removed the cultural rights of persons with disabilities from invisibility. It is proposed a clarification on cultural accessibility and people with disabilities, to present a history of the insertion of the cultural right of the person with disability in cultural policies, the contribution of the actors in the field of cultural policies and cultural rights of people with disabilities in the qualified insertion of the theme of culture in the current Brazilian Inclusion Law, as well as the current challenges of qualification and fortification of the agenda with cultural policies.